Effects of a lifestyle intervention module to reduce risk factors of metabolic syndrome in polycystic ovarian syndrome women in a public university, Malaysia - Dashti, Sareh (2018)
Introduction: Metabolic syndrome (MS) is common among women with polycystic ovarian syndrome (PCOS). Lifestyle education is considered a cornerstone for MS prevention. The aim of this study was to determine the effect of a lifestyle intervention module to prevent MS among PCOS patients. Methods: This study consisted of three phases. Phase one included screening of female UPM staff for PCOS based on the commonly used Rotterdam criteria and MS based on the International Diabetes Federation (IDF). A need assessment study was also performed to determine the educational needs of PCOS subjects. Phase two involved preparation of education module based on information-motivationbehavioral skills model and exercise sessions. Phase three was a randomized controlled trial (RCT) to validate the education module in 85 female UPM staff with PCOS. All participants underwent anthropometric and laboratory measurements at baseline and after 3 and 6 months of the study. Intervention group received education module through booklet and twice-weekly sessions. Results: The prevalence of PCOS was 12.59% (N=675). The mean BMI and WC of subjects with PCOS was 30.17 ± 1.75 kg/m2 and 90.73 ± 13.64 cm respectively. The questionnaires were validated based on face and content validity. The lifestyle intervention module was prepared to reduce MS criteria by reducing weight and abdominal obesity through healthy lifestyle. Intervention resulted in significant reduction in some of the MS criteria including weight (p<0.001), BMI (<0.001) and abdominal obesity (p<0.05), diastolic blood pressure (p<0.05) and the relative risk of MS (RR= 0.62). Conclusion: This study revealed that the lifestyle intervention module on healthy living can be used by physicians and health care providers to reduce risk factors of MS in Malaysian women with PCOS.